Flexible decoupled camera and projector fringe projection system using inertial sensors - Stavroulakis, Petros; Sims-Waterhouse, Danny; Piano, Samanta; Leach, Richard K. (SPIE, 2017)
Measurement of objects with complex geometry and many self occlusions is increasingly important in many fields, including additive manufacturing. In a fringe projection system, the camera and the projector cannot move independently with respect to each other, which limits the ability of the system to overcome object self-occlusions. We demonstrate a fringe projection setup where the camera can move independently with respect to the projector, thus minimizing the effects of self-occlusion. The angular motion of the camera is tracked and recalibrated using an on-board inertial angular sensor, which can additionally perform automated point cloud registration.